Survey of European patients assessing their own noncancer chronic pain: results from Spain. (June 2013) - Pérez, Concepción; Margarit, César; Serrano, Mar; ,
Abstract Objective: As part of the CHANGE PAIN international health campaign to improve pain management, patient surveys are being undertaken to explore how patients perceive their noncancer chronic pain and how they deal with it. Research design and methods: In Spain, 8695 patients completed this survey. The cross-sectional data were provided during routine visits to 893 physicians from different specialties. Pain intensity was assessed on two scales: a 5-point verbal rating scale (VRS) and an 11-point numerical rating scale (NRS). Results: Most patients were women (57%) in their late adulthood (45–64 years; 34%) or elderly (65 years or older; 53%). Pain duration of one year or longer was frequent (65%). Combined pharmacological treatment (51%) was more common than monotherapy (33%). The most frequently prescribed agents were nonsteroidal anti-inflammatory drugs, to be taken alone (18%) or together with weak opioids (15%), followed by weak (7%) or potent (6%) opioids in monotherapy; but there were many different treatments prescribed. Most patients had moderate (47%) or severe/extreme (34%) VRS rated pain. The mean intensity in the NRS was of 5.7 over 10. Many patients had pain above the level they could tolerate (38%) and most (55%) were not satisfied with their therapy. Their main goals were pain relief and reduction of side effects. Key limitations: Causal inductions are not possible in a cross-sectional research like this. Other clinically meaningful outcome measures in patients with chronic pain, such as patients' quality of life, were not gathered. Conclusions: Chronic noncancer pain management is poor. The uncoupling of VRS and NRS pain ratings reveals the high subjectivity of the pain experience, whilst the wide variation in treatment choices indicates that an optimal management strategy remains to be defined. Advances might be attained by boosting communication to tailor treatments to individual patients' perceptions.